ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA REWORK PADA PROYEK PEMBANGUNAN HOTEL ZEST AMBON - Siti Patimah Daeng Simamang; La Mohammat Saleh; Willem Gaspersz (Jurusan Teknik Sipil, 2023)
As a developing country, Indonesia cannot be separated from development and development in all fields, one of which is the construction and development of the construction business sector. The success of a project is largely determined by the good cooperation between the owner and the service provider. If the technical implementation is not good, it will have a bad impact on project performance, one of which is rework. The word rework in the Big Indonesian Dictionary is translated as rework or rework. Rework on construction projects is caused by errors in planning, wrong work procedures, and lack of supervision and can result in several losses, such as cost, time, and quality of work. This research was conducted by interviewing and distributing questionnaires to the construction project of Hotel Zest Ambon as many as 30 respondents. Respondents selected were implementers, supervisors, foremen, and workers. The questionnaires distributed were related to the factors causing the rework on the Zest Ambon Hotel construction project, which is located on Jl. Imam Bonjol, Kel Ahusen, Sirimau, Ambon City. Then the research results were processed using SPSS 26, using 4 methods of analysis, namely validity test, reliability test, descriptive analysis, and factor analysis to get the factors causing the rework and the dominant factors causing the rework. The results of the research show that there are three factors that cause rework, namely design and documentation factors with a mean value of 4.53, resource factors with a mean value of 4.37, and managerial factors with a mean value of 3.80. And the dominant factor is the design and documentation factor with Eigenvalues ​​> 1, which is 1.50.